2012
DOI: 10.1016/j.appet.2011.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meal frequency and snacking on food demand in mice

Abstract: Ad libitum feeding patterns in mice show substantial differences between laboratories, in addition to large individual and time-of-day differences. In the present study, we examine how mice work for food when access to food is temporally restricted and so they are forced to take discrete meals. In a first experiment, separate groups of ICR:CD1 mice were given access to food for 4, 8 or 16 opportunities or meals per day, with the duration of access at each opportunity adjusted reciprocally so that the total tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…For the five studies, the number of feeding occasions in the EF manipulations varied greatly, ranging from 1 to 24 feeding occasions per day, and the experimental period ranged from 3 to 28 days ( 35 39 ). Of the three studies reporting on intake, all found no significant difference in consumption between EF conditions ( 36 , 37 , 39 ). Of the four studies reporting on body weight, three found no significant difference between EF conditions, and one found significantly less body weight gain in the higher EF condition ( 35 , 36 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…For the five studies, the number of feeding occasions in the EF manipulations varied greatly, ranging from 1 to 24 feeding occasions per day, and the experimental period ranged from 3 to 28 days ( 35 39 ). Of the three studies reporting on intake, all found no significant difference in consumption between EF conditions ( 36 , 37 , 39 ). Of the four studies reporting on body weight, three found no significant difference between EF conditions, and one found significantly less body weight gain in the higher EF condition ( 35 , 36 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 93%
“…Of the three studies reporting on intake, all found no significant difference in consumption between EF conditions ( 36 , 37 , 39 ). Of the four studies reporting on body weight, three found no significant difference between EF conditions, and one found significantly less body weight gain in the higher EF condition ( 35 , 36 , 38 , 39 ). Cardiometabolic/hormonal measures taken varied between studies, but insulin and insulin-like growth factor-1 were measured in two studies, with inconsistent outcomes found (one study found significantly higher insulin in the higher EF condition, while the other study found significantly lower insulin in the higher EF condition; one study found significantly higher insulin-like growth factor-1 in the higher EF condition, while the other study found no difference among the EF conditions) ( 38 , 39 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although such an exposure always occurred during the active phase of the nycthemeral cycle, it by no means fully recapitulates the human condition where reward choices are permanent. One means to circumvent this limit might consist of housing the animals in operant chambers (46) with permanent choices between wheel running and feeding. Our future experiments, aimed at focusing on this paradigm, will surely help to refine the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as with operant chamber studies from other investigators, a similar "N" was used, with similar statistical power (e.g. [43,44]). We furthermore found results in the mouse model very consistent with what has been observed in human populations.…”
Section: Discussionmentioning
confidence: 99%